PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA - Partasiwi, Nurashri; Kirana, Arinta Rara; Arga, Kharisma Idola; Pratama, Elvandri Yogi (STKIP PGRI Bandar Lampung, 2021)
This study aims to determine the effect of the cooperative learning model type GI (Group Investigation) on students' mathematical communication skills. This research is a quantitative research with a type of quasi-experimental research. The population in this study were all students of class X TO at SMK Negeri 5 Bandar Lampung even semester of the 2020-2021 academic year, amounting to 179 students and sampling using cluster random sampling technique so that two classes were obtained as the research sample, namely class X TO 4 as the experimental class. as many as 36 students and class X TO 5 as the control class as well as 36 students. Data were collected through tests of mathematical communication skills in the form of essay tests. Based on the t test conducted, it was obtained t count > t table which was 16.50 > 1.69, which means that there was a significant influence on the cooperative learning model type GI (Group Investigation) on students' mathematical communication skills in class X TO SMK Negeri 5 Bandar Lampung Even Semester of The 2020-2021 Academic Year.